Legal Protection of Patients Against Overlapping Authority Among Medical Specialists After the Enactment of Law Number 17 Of 2023 On Health - Desy Kartika Ningsih; Hasanah; Rahayu Eviriyanti; Arens Hehega; R. Deltanto Sarwi Diatmiko; Tetty Melina (Lembaga Bale Literasi, 2026)
Law Number 17 of 2023 on Health introduces significant changes in the governance of the medical profession in Indonesia, including provisions concerning specialist medical personnel, collegiums, and the practice licensing system. However, the increasingly multidisciplinary development of medical science creates the possibility of overlapping authority among medical specialists in treating patients. This situation may create legal uncertainty, disputes over professional authority, and may potentially interfere with the fulfillment of patients' rights if it is not clearly regulated. This study aims to analyze the forms of legal protection for patients in facing overlapping authority among medical specialists after the enactment of Law Number 17 of 2023 on Health, while also formulating a model for strengthening legal protection that emphasizes patient safety. The method used is normative juridical research with statutory and conceptual approaches. The results show that Law Number 17 of 2023 has provided a legal foundation for protection through the regulation of competency standards, professional standards, professional discipline, informed consent, and mechanisms of medical personnel accountability. However, these provisions have not yet explicitly regulated mechanisms for resolving conflicts of authority among medical specialists whose fields of competence intersect. Therefore, harmonization of technical regulations, strengthening of clinical privileges in hospitals, and the establishment of professional dispute resolution mechanisms oriented toward patient interests and safety as the main priority are required.